Appoggiature: Parole scelte per raccontare Luca Ronconi - Sicca, Benedetto (Mimesis Journal, 2015)
The director and writer Benedetto Sicca recalls the time he spent working as one of Ronconi’s assistants. He chooses the form of a ABCs of memories and concepts that are relevant in the activity of one of the most influential theatre director in contemporary theatre; here remembered with a personal and affectionate stance.